Go-Trash Berbasis Website (Studi Kasus di Dinas Lingkungan Hidup dan Kehutanan Kab. Sumedang) - Deris Santika; Santi Papiyani (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2019)
This study discusses the problem of garbage collection service. Starting from the implementation of waste collection process that there are problems, one of them is the officers that are not available in all areas in Sumedang district, especially in Sumedang city area, with the condition that the unserved communities throw garbage in the arbitrary place like on the banks of the river. To overcome these problems can be applied information technology. Use of such information technology can help solve the problems encountered. One of them is with the application of technology in the form of garbage pickup service to the public. With this application people can order officers from the Environment and Forestry Agency (DLHK) to pick up garbage by filling in the data themselves and the location of the garbage pickup. System designed and built Website Application Go-trash in the design of application design Go-trash (pick up garbage) using a prototype model with the stages of problem identification with the method of interview and observation of the resulting data will be determined alternative solutions. If the solution has been obtainedthen the next stage is to analyze the needs of the system to be cre ated, after it will be designed prototype of the system which will be implemented using programming language. If the system is finished then it will be evaluated and tested. It is hoped that with this application, people can easily get garbage pickup servi ce from DLHK officers and it is hoped there will be no more garbage accumulation in society.